Анализ трансмиссий современных легкобронированных колесных военных машин и их влияния на параметры подвижности - Стримовский, Сергей Викторович; Слюсаренко, Ю. А.; Соловьев, В. М. (НТУ "ХПИ", 2014)
В статті виконано порівняльний аналіз конструктивних відмінностей різних типів трансмісій, які використовуються на легкоброньованих колісних військових машинах, їх технічних характеристик та параметрів рухомості. Визначені напрямки підвищення рухливості легкоброньованих колісних військових машин.

In article the comparative analysis design features various types of transmissions which are applied on easy-armor wheel military vehicles, their technical characteristics and mobility parameters is made. Directions of increase of mobility of is easy-armor wheel military vehicles are defined.
The analysis of transmissions modern easy-armour wheel military vehicles and their influence on mobility parameters
Keywords: легкобронированные колесные военные машины; легкобронированные машины; военная техника; бронетанковая техника; трансмиссия; подвижность военных машин